The Tangled Evolutionary Legacies of Range Expansion and Hybridization. (September 2016) - Canestrelli, Daniele; Porretta, Daniele; Lowe, Winsor H.; Bisconti, Roberta; Carere, Claudio; Nascetti, Giuseppe
Abstract : Spatial sorting of dispersal-enhancing traits has been implicated in substantial directional changes in the phenotypic and genotypic makeup of populations undergoing range expansion. We explore here the evolutionary consequences of such changes when two divergent lineages come into secondary contact. We combine instances from the study of contemporary range expansions and historical hybridizations, and highlight links between dispersal, sexual, and physiological traits during the non-equilibrium conditions imposed by range expansions. We argue that a stronger research focus on processes of spatial sorting of multiple traits will improve our understanding of subsequent hybridization dynamics and their evolutionary outcomes, including genomic introgression and speciation. Trends: Mounting data show that substantial, rapid, and deterministic changes in the phenotypic and genotypic makeup of populations can occur during range expansions by spatial sorting of dispersal-related traits. Traits associated with dispersal also influence other fundamental biological processes, such as reproduction, physiology, and behavior. Dispersal, sexual, physiological, and behavioral traits are of crucial importance for hybridization dynamics between divergent lineages upon secondary contact. A stronger focus on multiple trait associations and spatial sorting during range expansion could improve our understanding of subsequent hybridization events and their evolutionary outcomes.